Os impactos externos da independência dos Bancos Centrais - Griffin, Carroll Howard (2010)
The term "central bank independence" (or abbreviated, CBI) can be broadly defined as the degree of freedom of the central bank to pursue monetary policy without interference from political considerations. The idea of central bank independence has been widely accepted over the last several decades by many countries around the world, both developed and developing. Since being first written about academically in the late 1980s, many countries have come to adopt this policy and many governments have come to recognize this as standard procedure. As such, many countries around the world granted autonomy to their central banks during the 1980s and 1990s. The majority of past studies have examined primarily the impact of central bank independence on inflation. however, the additional theoretical benefits are much more far reaching, the result of a more stable and prosperous macroeconomic environment. Additionally, there is only now sufficient data to empirically determine whether many of these claims are true. This study examines central bank independence in developing countries of Latin America and Asia as well as selected developed countries to determine what actual impact an autonomous central bank has had. It also examines such phenomena as financial crises (including the current global crisis of 2008-2009), inflation targeting, legal systems, country development and fiscal policy to determine the effects of these items on not only inflation, but the broad spectrum of macroeconomic outcomes. Although there is some empirical evidence to support the benefits of central bank independence, it is limited in scope to certain areas.